Evaluation of legal translations: PIE method (Preselected Items Evaluation) - Kockaert, Hendrik J.; Segers, Winibert (The Journal of Specialised Translation, 2017)
This article is situated in the field of translation evaluation and consists of two parts. The first part is dedicated to the different meanings of the term 'translation evaluation' and the implications for evaluation approaches. The term 'translation evaluation' may refer to the translation product, the translation process, the translation service and the competence of the translator. Product, process, service and competence of the translator require different evaluation approaches. In the second part of the article we illustrate in a case study a method for evaluating the translation product: the PIE method (Preselected Items Evaluation).